2004
DOI: 10.1086/425610
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intermittent Rifampin and Pyrazinamide Therapy for Latent Tuberculosis Infection in a Targeted Tuberculin Testing Program

Abstract: Despite the use of DOPT, intermittent dosing, and vigilant monitoring throughout therapy, RZ was associated with an unacceptable risk of hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 27 publications
(46 reference statements)
0
10
1
Order By: Relevance
“…Previous studies have found inconsistent associations between adherence to LTBI treatment and these factors. 810 Also, while the study by Reichler, et al found that recent TST converters were most likely to complete LTBI treatment, 6 this was not a significant factor associated with treatment completion in the current study. Interestingly, study sites differed significantly in treatment completion.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have found inconsistent associations between adherence to LTBI treatment and these factors. 810 Also, while the study by Reichler, et al found that recent TST converters were most likely to complete LTBI treatment, 6 this was not a significant factor associated with treatment completion in the current study. Interestingly, study sites differed significantly in treatment completion.…”
Section: Discussioncontrasting
confidence: 57%
“…1993; Donald 2010). Further, a study including 423 immigrants found PZA‐associated hepatotoxicity to be correlated with age: the odds of hepatotoxicity rising by 1.07 times per year of age increase (Priest et al. 2004), and a study investigating PT found drug‐associated hepatitis increased significantly with age, from <1% in those aged 0–19 years to 5% in those aged 60 years or more (Ormerod & Horsfield 1996).…”
Section: Overcoming the Barriersmentioning
confidence: 99%
“…10,34 The recommendation of daily rifampin and pyrazinamide for 2 months was discontinued 34 after it was shown to have unacceptable liver toxicity. 35 The CDC has issued no clear recommendation on how long latent TB infection prophylaxis must be given before a TNF-a inhibitor may be added, but it is preferable for a patient to receive the full 9-month course of therapy. However, the patient's clinical course may require earlier initiation of therapy, and the clinician must balance the possible increased risk of active TB with the morbidity suffered from protracted disease.…”
Section: Treatment Of Latent Tb Infectionmentioning
confidence: 99%